'It's Too Easy to Say that Institutions are Decolonizing': An Interview with Senate House Library's Richard Espley and Leila Kassir. (28th December 2021) - Pyke, Sarah
Abstract: In 2020, as public protest against anti-Black police brutality surged globally, institutional public statements in support of the Black Lives Matter movement proliferated. Universities, libraries, museums, and other cultural institutions rushed to deplore racist violence and express their commitment to anti-racist and decolonial practice. Rather than release a statement of their own, staff at Senate House Library – the central library for the University of London and the School of Advanced Study – chose instead to pursue and embed a fledgling piece of reparative archival work, the Collections Inclusion Review, alongside their continuing efforts to improve the inclusivity and accessibility of their collections, particularly of literatures in English. This interview is a transcribed and edited version of a conversation with the two Senate House Library staff members leading this work: Richard Espley, now Head of Collections (and formerly Head of Modern Collections), and Leila Kassir, Academic Librarian for British, Irish, USA, Latin American, Caribbean, and Commonwealth Literature. The discussion ranged across issues of provenance, archive description, library layout, and the future of English as a discipline, urging attention to and amelioration of the exclusionary aspects of library practice. While critiquing institutional approaches to the legacies of colonialism, past and present, both interviewees expressed reservations about widespread claims to have 'achieved' decolonization, stressing that such calls are contingent on surrounding structures and processes, and suggesting that such radical dismantling remains a long-term aspiration, rather than a quick-fix solution.